THE ROLE OF POLITICAL COMPETITION BETWEEN AUDIT FINDINGS AND AUDIT OPINIONS - Rahmawati, Dinda Millenia; Achmad, Komarudin (Jurnal Akuntansi Kontemporer, 2024)
Research Purposes. This study aimed to determine the influence of audit findings on audit opinion involving the moderating variable of political competition among regencies/city governments in Indonesia.Research Methods. The secondary data are analyzed quantitatively utilizing binary logistic regression and MRA (Moderated Regression Analysis), processed by SPSS version 25 software. The population involves the entire 508 local governments of city-regencies in Indonesia, from which 395 sample cities/regencies in Indonesia in fiscal year 2016 were selected using purposive sampling.Research Results and Findings.  The results showed that audit findings on internal control system weaknesses and non-compliance with legislation have a negative and significant effect on audit opinion, which means that more audit findings lessen the chance for the government to obtain an unqualified opinion. In addition, political competition strengthens the effect of audit findings of non-compliance with legislation and weaknesses in the internal control system on audit opinion. It implied that local governments in Indonesia should enhance internal controls and compliance and account for political factors to improve audit opinions.